Properties and characteristics of steam-exploded donkey bone powder and corresponding whole wheat cookies - Yue Li; Xinru Qiu; Yuanshuai Jiang; Feng Kong; Guiqin Liu (Food Chemistry: X, 2024)
Steam explosion was found to be the most effective preparation method for donkey bone powder, compared with non-treatment, autoclave and steam processing. And the effect of steam-exploded donkey bone powder (SEDBP) on the quality characteristics of whole wheat cookies was evaluated. Compared with untreated powder, particle size of SEDBP was reduced by 55.60 %, while oil- and water-holding capacity, water solubility and ABTS radical-scavenging rate significantly increased by 13.94 %, 26.86 %, 298.26 % and 91.47 %, respectively. Steam explosion enhanced protein digestibility from 32.17 % to 71.43 %, increased the Ca2+ release rate from 37.47 % to 47.82 %, and increased the release of 11 amino acids during digestion. SEDBP reduced the solvent retention capacity of flour blends and improved the color, hardness and spread ratio of whole wheat cookies. Cookies with 30 % SEDBP addition had better flavor, texture and scored the highest on overall acceptability. The results will help expand animal bone applications and develop nutrition-fortified foods.